DEVELOPING THEIR EXPERIMENTAL COMPETENCE BY TEACHING STUDENTS HOW TO MAKE OBJECTS OF ALL THREE DIMENSIONS IN A 3D PEN (Academicia Globe: Inderscience Research, 2023)
A 3D pen is a tool used to draw different three-dimensional shapes. Its main raw materials are polymer materials. "D" is derived from the English word doodler, which means "voluntarily dealing with something else." For example, when you're talking on a phone or watching TV, you're voluntarily drawing different shapes and pictures.